Influence of environmental variables on the water quality of a coastal tropical lagoon in northern Brazil - Pereira, Maria Eduarda Garcia de Sousa; Asp Neto, Nils Edvin; Moura, Hanna Tereza Garcia de Sousa; Nunes, Zélia Maria Pimentel (Arquivos de Ciências do Mar, 2017)
The coastal lagoons play important ecological and socio-economic roles due of their high productivity and multiple uses of the water. This research aimed to evaluate the time variation of a few environmental variables of the Salina Lagoon (northeastern Pará State), whose dynamics display peculiar characteristics as to seasonality of outstanding spring tides, and humic substances derived from the predominant mangrove forest in its draining basin. The water was monitored monthly over a year’s period for twelve months, based on the estimates of temperature, salinity, dissolved oxygen, pH, conductivity, turbidity, transparency, depth and rainfall. Their results showed that only salinity, conductivity and pH values showed significant differences between the rainy and dry seasons, highlighting the influence of rainfall on the lagoon. The Principal Component Analysis has explained 71.9% of the data variation, with Component 1 underscoring the influence of seasonality on water transparency, conductivity and rainfall, and Component 2 underscoring the influence of spring tides and early rainy season on pH and turbidity. All those features can impose, in certain periods, extreme conditions to the aquatic biota